Research advances of Netherton syndrome - Xiaoxuan CHEN; Guiyue CAI; Ruitao ZOU; Rongyi CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Netherton syndrome (NS) is a rare recessive syndromic ichthyosis due to mutations in the SPINK5 gene characterized by a triad of congenital ichthyosiform erythroderma (CIE) and/or ichthyosis linearis circumflexa (ILC), hair shaft abnormalities, and elevated IgE levels. However, NS patients often suffer from misdiagnosis, delayed treatment, or even ineffective therapy for the triad is not always complete. To achieve identification early and intervention effectively, the paper comprehensively reviewed the pathogenesis progression, clinical features, histopathology and immunohistochemistry, diagnosis and differential diagnosis, and treatment advancement of the NS.